Effect of culture media and auxin on growth and glucosinolate accumulation in the hairy root cultures of mustard (Brassica juncea) - Bong, Sun Ju; Park, Jennifer; Kwon, Do Yeon (Journal of Phytology, 2022)
Brassica juncea is a vegatable that are rich in glucosinolate (GSL) content. The hairy root (HR) cultures system is one of the most useful tools for secondary metabolites (SM) biosynthesis under various growth conditions. In the past, GSLs were mostly used as biopesticides in agriculture, anti-nutritional factors in fodder, and flavors in condiments. However, in recent days, GLSs have received much attention in human health. To investigate the growth response and variation of GSLs accumulation, HRs of mustard were grown in different growth media and auxins. The HRs growth pattern varied largely under the treatments of growth media and auxin. The full-strength SH media responded greatly for achieving the highest dry weight (DW) followed by the ½ SH media and the lowest DW was obtained in full-strength MS media. In all the auxin treatments the HRs production was higher than that of the control. It was noted that at higher NAA and IBA concentrations HR production was increased than that at the lower concentrations. In addition, different growth mediums significantly influenced the GSLs accumulation in mustard HR. The results revealed that ½ B5 media showed the highest total GSLs content followed by B5 and ½ SH. Treatment of mustard HRs with auxins such as IAA and IBA negatively influenced the accumulation of GSLs except for 4-methoxyglucobrassicin. We, therefore, suggest that HRs are a viable option for improving the GSLs content from the HR culture of mustard and that SH and ½ B5 medium provides an alternative approach for mass production of HRs and GSLs in mustard, respectively.